2020
DOI: 10.1038/s41588-020-00732-8
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific and interferon-inducible expression of nonfunctional ACE2 through endogenous retroelement co-option

Abstract: Angiotensin-converting enzyme 2 (ACE2) is an entry receptor for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and a regulator of several physiological processes. ACE2 has recently been proposed to be interferon (IFN) inducible, suggesting that SARS-CoV-2 may exploit this phenomenon to enhance viral spread and questioning the efficacy of IFN treatment in coronavirus disease 2019. Using a recent de novo transcript assembly that captured previously unannotated transcripts, we describe a new isoform… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
99
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(111 citation statements)
references
References 39 publications
11
99
1
Order By: Relevance
“…2a, 3a). However, recent reports suggest this signal is driven by an ACE2 isoform that lacks the viral binding domains and is unlikely to encode a functional receptor 19,20 .…”
Section: Resultsmentioning
confidence: 99%
“…2a, 3a). However, recent reports suggest this signal is driven by an ACE2 isoform that lacks the viral binding domains and is unlikely to encode a functional receptor 19,20 .…”
Section: Resultsmentioning
confidence: 99%
“…However, the degree of induction of either form was lower than that seen for bona de ISGs. Previous studies in normal human bronchial epithelium (NHBE) did not reveal an interferon response of the native ACE2 promoter 4,5 suggesting differences between cell types or growth conditions. The mouse Ace2 gene is also induced by cytokines through a STAT5-based enhancer in the second intron 8 and a DHS site is located in the equivalent location in the human ACE2 gene in SAEC and lung tissue.…”
Section: Interferons Regulate Theace2locus In Human Airways Cellsmentioning
confidence: 90%
“…Single cell RNA sequencing (scRNA-seq) studies have revealed that ACE2 expression in type II pneumocytes is induced by interferons 3 , suggesting that the presence of an autoregulatory loop could result in increased viral infection. Recent studies 4,5 have identi ed a novel short form of ACE2, called dACE2, that originates from an intronic promoter activated by interferons, calling into question that transcription of the full length native ACE2 is under interferon control. Onabajo et al 5 used ENCODE data for chromatin modi cation marks (H3K4me3, H3K4me1 and H3K27ac) as well as DNase I hypersensitive (DHS) sites in cell lines to label putative regulatory elements at the newly identi ed exon (ex1c) located within intron 9 of the ACE2 gene.…”
Section: Introductionmentioning
confidence: 99%
“…Since our lung transcriptome quantifies steady-state expression changes of all cell types, it is conceivable that we do not detect up-regulation in a smaller population of infected cells. Besides, two recent studies ( 54 , 55 ) show alternative splicing of ACE2 in humans, up-regulated by both viruses and IFNs. Therefore, it may be important to quantify different Ace2 isoforms’ expression in infected mouse lungs by immunohistochemistry, by single-cell methods, or by in situ hybridization to resolve specificity and kinetics of responses.…”
Section: Resultsmentioning
confidence: 95%